2018
DOI: 10.1371/journal.pone.0203643
|View full text |Cite
|
Sign up to set email alerts
|

Complication patterns in patients undergoing venoarterial extracorporeal membrane oxygenation in intensive care unit: Multiple correspondence analysis and hierarchical ascendant classification

Abstract: BackgroundTreatment by venoarterial extracorporeal membrane oxygenation (VA-ECMO) is widely used today, even though it is associated with high risks of complications and death. While studies have focused on the relationship between some of these complications and the risk of death, the relationship between different complications has never been specifically examined, despite the fact that the occurrence of one complication is known to favor the occurrence of others. Our objective was to describe the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…In total, 25 studies detailing 5896 adult patients that reported on the use of RRT and ECMO were included ( Table 1 ) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Twenty-four studies were observational in nature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], while one study was a randomised controlled trial (RCT) [ 52 ]. For our quantitative analysis, we included 24 observational studies (5855 patients), while the findings of the RCT were reported separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 25 studies detailing 5896 adult patients that reported on the use of RRT and ECMO were included ( Table 1 ) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Twenty-four studies were observational in nature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], while one study was a randomised controlled trial (RCT) [ 52 ]. For our quantitative analysis, we included 24 observational studies (5855 patients), while the findings of the RCT were reported separately.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled overall mortality ( Figure 1 ) in patients due to the use of RRT on ECMO (24 studies) was 62.9% (95% CI: 56.0–69.6%). Subgroup analysis found no significant differences ( p = 0.57) between in-hospital mortality (14 studies, 60.1%, 95% CI: 50.1–69.8%) [ 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 42 , 43 , 45 , 48 , 49 , 50 ], ICU mortality (3 studies, 67.3%, 95% CI: 60.1–74.1%) [ 28 , 29 , 32 ], 30-day mortality (3 studies, 68.4%, 95% CI: 58.0–77.9%) [ 41 , 44 , 47 ], and 90-day mortality (3 studies, 57.0%, 95% CI: 17.6–92.0%) [ 30 , 40 , 46 ]. Only one study mentioned overall mortality [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V–A ECMOで懸念される合併症として,血栓性の合併症と出血性の合併症が挙げられる。V–A ECMOを施行することで5.3%の患者で脳梗塞を発症するが,生命予後には関連しないとする報告 や,約半数に死亡に関連する多量の出血性合併症を起こすとの報告 もある。初療の時点で重症頭部外傷が否定できない場合や,FAST陽性例では,V–A ECMOの導入に慎重にならざるを得ない。…”
Section: 考  察unclassified
“…ECMO can be either veno-venous cannulation (VV), which is used predominantly in hypoxic respiratory failure states like acute respiratory distress syndrome or veno-arterial cannulation (VA), which is the main or preferred modality for cardiac support system like postoperative cardiac surgery and cardiogenic shock. The survival rate for VV-ECMO is 60% and for VA-ECMO is 45% when death is imminent [1][2][3][4]. Sepsis can be a reason for initiating ECMO, and on the other hand, patients can develop sepsis on ECMO too.…”
Section: Introductionmentioning
confidence: 99%